VARIASI BAHASA DALAM DIALOG TOKOH FILM TOBA DREAMS GARAPAN BENNY SETIAWAN - Leo Wira Hardiono (sarasvati, 2019)
Language variety is a variant of a language according to usage. This study was conducted to determine the use of language variations in terms of speakers in the movie Toba Dreams director Benny Setiawan. In the film there are some characters who have different ethnic backgrounds and sociology. This study aims to describe dialect and sociology in the dialogue between characters in the movie Toba Dreams. The method used in this research is qualitative descriptive. Provision of data is done by the method refer, by listening and understand the language data in the form of spoken language in the data source dialogue between characters. Technique used is technique record and record. Results from the study. 1) the form of dialect variation, 2) sociolek in dialogue between characters. The results of this study can be used as a reading material for the understanding of the community when viewing the movie Toba Dreams.